Pengembangan Media Tak Tik Butarna Berbasis STEAM pada Pembelajaran Tematik Kelas 1 SD - Twiningsih, Anik (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of this study is to develop STEAM-based learning media (Science, Technology, Engineering, Arts, Mathematics) in grade 1 thematic learning to improve critical thinking skills and culture of scientific literacy in grade 1 students. This media was developed based on the STEAM approach, so the use of media through the syntax of analyzing, synthesizing, making conclusions and organizing strategies and tactics. The excellence of this innovative work focuses on improving critical thinking skills and scientific literacy. This type of research is research and development (Research and Development) with ADDIE design (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the study before using STEAM-based butik media, it is known that the average class of students’ critical thinking skills is 74.80 and the average science literacy class is 73.61. After using STEAM-based typewriter media it can be seen that the average class of students’ critical thinking skills is 86.67 and the average science literacy class is 88.67. The results of this study prove that STEAM-based non-typed media developed can improve students’ critical thinking skills so that it has a positive impact on scientific literacy. The conclusion of this study is that new learning media developed can increase the activeness of students and ultimately have a positive impact on student learning outcomes.